CLINICAL EPIDEMIOLOGY OF LYMPHATIC FILARIASIS AND COMMUNITY PRACTICES AND PERCEPTIONS AMONGST THE ADO PEOPLE OF BENUE STATE, NIGERIA - Agbo, Omudu Edward; Ochanya, Ochoga Jennifer (African Journal of Infectious Diseases (AJID), 2011)
As part of efforts to initiate lymphatic filariasis elimination activities in Benue State, this study employed the use of lymphatic filariasis–related clinical signs as rapid diagnostic features, immunochromatographic card test (ICT) to detect circulating filarial antigen (CFA) and questionnaire to investigate community perceptions and beliefs. 81 (32.6%) out of the 248 persons were positive for circulating filarial antigen (CFA). Infection rates denoted by CFA ranged from 41 (46.1%) in Uffia to 1(6.6%) in Ijigbam districts. Distribution of community ICT prevalence showed a significant variation (X2, P < 0.05). The prevalence of clinical signs and/or symptoms in the communities also showed significant variations (X2, P < 0.05). Community hydrocoele prevalence ranged from 8 (9.0%) in Uffia to 1(6.6%) in Ijigbam. The overall hydrocoele prevalence was 21 (8.5%), while the overall lymphoedema prevalence was 16 (6.4%) and women accounted for 14 (87.5%) of persons with swollen limbs. Only about 14 (15.9%) of unaffected respondents knew that lymphatic filariasis is transmitted through mosquito bites, this differ significantly from affected respondents 10 (66.6%) (X2, P < 0.05). The communities’ capacity to protect themselves is hindered by a lack of understanding of the true cause, symptoms, transmission route and prevention of the disease. Our study demonstrates the need for the development of health education programmes that will enable people to protect themselves against mosquito bites. As Nigeria commence her lymphatic filariasis elimination programmes, there is an urgent need to develop morbidity management activities that will alleviate the burden of patients.